2012
DOI: 10.1055/s-0032-1327628
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Parathyroid Glands and their Anatomical, Clinical and Surgical Implications

Abstract: Ectopic parathyroid glands result from aberrant migration during early stages of development and lack of successful identification may lead to lack of success in parathyroid surgery. They constitute a common etiology of persistent or recurrent hyperparathyroidism, when they are missed at initial diagnosis. Their prevalence is about 2-43% in anatomical series and up to 16% and 14% in patients with primary and secondary hyperparathyroidism, respectively. Ectopic inferior parathyroids are most frequently found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0
27

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(119 citation statements)
references
References 34 publications
0
92
0
27
Order By: Relevance
“…4 Imaging studies have reported low incidence (1.4%) of ectopic parathyroid adenomas in patients who underwent investigation for primary hyperparathyroidism. The actual prevalence of MPA is unknown but has been reported to be 6-30%.…”
Section: Epidemiologymentioning
confidence: 99%
“…4 Imaging studies have reported low incidence (1.4%) of ectopic parathyroid adenomas in patients who underwent investigation for primary hyperparathyroidism. The actual prevalence of MPA is unknown but has been reported to be 6-30%.…”
Section: Epidemiologymentioning
confidence: 99%
“…The superior and inferior parathyroid glands develop from the dorsal wing of the fourth and third pharyngeal pouches, respectively, along with the thymus. The inferior glands can migrate with the thymus; hence they are more likely to be found in ectopic locations (2,5). Previous cases of functional, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of PHPT cases are asymptomatic and are detected incidentally with hypercalcaemia on bloodwork. PHPT results from the intrinsic abnormal change in 1 or more of the 4 parathyroid glands, in which excess parathyroid hormone (PTH) is secreted autonomously (1,2). PHPT is commonly caused by a single parathyroid adenoma (75 to 85%), parathyroid gland hyperplasia (10 to 20%), multiple adenomas (4 to 5%), and rarely carcinoma (1%) (1,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that parathyroid glands can be found in aberrant locations, mainly in the thyroid parenchyma or in the mediastinum. 3 The high incidence of ectopic inferior parathyroid glands has been attributed to abnormal migration during embryogenesis. Since parathyroid glands lack capsular fixation, an ectopic parathyroid gland may also develop from a gland that is initially present in a normal anatomic position but which enlarges and is displaced to an ectopic location where there is little resistance.…”
Section: Discussionmentioning
confidence: 99%